Pendidikan Multikultural di Pondok Pesantren - Rifa’i, Muhadditsir; Khaeriyah, Ery (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
This multiculturalism education, has been widely studied with different scientific perspectives. The diversity of the origin of the population, students and school students in Pondok Buntet Pesantren, according to researchers, is important to know the concept of multicultural education in the Pondok Buntet Pesantren environment, Cirebon. Because of that, the researcher derivates his study in the following research questions: What concept of multicultural education is being pursued in the Pondok Buntet Islamic Boarding School environment? To what extent are the roles of pesantren leaders and leaders in the concept of multicultural education being pursued in the Pondok Buntet Pesantren environment? This research is categorized as inductive qualitative research, with a case study method approach. The data analysis technique is the concept of descriptive-exploratory analysis involving three components of analysis, namely data reduction, data display (data dislay), and conclusion drawing (verification).